The Role of the Teacher in Realizing the Pancasila Student Profile - La Marwin (Universitas Negeri Makassar, 2022)
This scientific article discusses the role of teachers in creating the profile of Pancasila students at SMAN 1 Limboto. In order to realize its vision in the field of education, the government has established an independent curriculum policy in the hope that students will be born who can apply Pancasila values in the school environment by maximizing the important role of the government, society/parents, and the school in this case the teacher. The figure of the teacher becomes very crucial to create the profile of pancasila students with various roles that can be applied in school. As a result, the students of SMAN 1 Limboto have been able to apply some of the values of the Pancasila student profile on several dimensions, namely the dimension of faith and piety, the dimension of cooperation, and the creative dimension. The application of the dimension in question, for example, faith and piety can be seen with the activities of morning zikr, noon prayer together, cultivating salam and almsgiving. The mutual cooperation dimension is seen in the activity of cleaning the classroom and school environment together. As for the creative dimension, it can be seen in the students' creativity exhibition activities on their own initiative.